Digital Marketing Design Through Social Media For Abon Taminye Latuhalat Products In Tupa Hamlet Latuhalat Village, Ambon City - Meilissa Claudya Kalatty; Ambarwati Soetiksno; Julius Buyang; Stenly Ronaldo Titioka; Frangky Jansen Louth (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to carry out digital marketing of Abon Taminye Latuhalat through social media to help UKM Merdeka Bergiat Group increase their product marketing potential. Small and Medium Enterprises or abbreviated UKM is a type of business that plays an important role in increasing the economic growth of a country. One of the SMEs in the city of Ambon, especially in the village of Latuhalat, is a fish floss business with the name